HUBUNGAN KEJADIAN SECTIO CAECAREA DENGAN IBUBERSALIN YANG BERISIKO DI RSUDDr. R. GOETENG TAROENADIBRATA PURBALINGGA TAHUN 2011 - Ikit Netra Wirakhmi (Viva Medika, 2012)
Background: Factors predisposing to direct cause of death in women is influenced by severalfactors, the mother's health is at risk. one of the categories of maternal risk is prematurerupture of membranes. When the incident occurred above sectio caesarea it must be done tosave the lives of mothers. Preliminary survey conducted in hospitals Hospital dr. R GoetengTaroenadibrata on February 15, 2012 that the incidence of birth sectio caecarea in 2010 was305 out of 1120 deliveries (27.2%) and Banyumas Hospital events sectio caecarea labor in2010 was 361 out of 1421 deliveries (25.4%) Objective: To determine the incidence of sectio caecarea relationship with birth mothers whoare at risk in hospitals Dr. R. Goeteng Taroenadibrata Purbalingga in 2011. Methods: This study is a retrospective descriptive study korelasidengan approach. Thesamples are sampling jenuh, samples of this research is all ibu bersalin.Sampel 1256respondents in this study. The analysis used data analysis univariat dan bivariate analysisusing chi-square method Results: Labor Sectio Caecarea many as 336 people (26.8%), mothers who risk as much as612 people (48.7%) and from the data analysis bivariat didapatkan bahwa Ï‡Â² count> Ï‡Â² table(118.277 > 3,841) with the corelation 0,293 coofisien Ho rejected and Ha accepted Conclusion: There is a relationship between the incidence of birth sectio caecarea with birthmothers who are at risk Keywords: Labor Sectio Caecarea, Mother Maternity Risk.